Therapeutic Effects of Breviscapine in Cardiovascular Diseases: A Review - Gao, Jialiang; Chen, Guang; He, Haoqiang; Liu, Chao; Xiong, Xingjiang; Li, Jun; Wang, Jie (Frontiers in Pharmacology, 2017)
Breviscapine is a crude extract of several flavonoids of Erigeron breviscapus (Vant.) Hand.-Mazz., containing more than 85% of scutellarin, which has been traditionally used in China as an activating blood circulation medicine to improve cerebral blood supply. Accumulating evidence from various in vivo and vitro studies has shown that breviscapine exerts a broad range of cardiovascular pharmacological effects, including vasodilation, protection against ischaemia/reperfusion (I/R) , anti-inflammation, anticoagulation, antithrombosis, endothelial protection, myocardial protection, reduction of smooth muscle cell migration and proliferation, anticardiac remodelling, antiarrhythmia, blood lipid reduction and improvement of erectile dysfunction. In addition, several clinical studies have reported that breviscapine could be used in conjunction with Western medicine for cardiovascular diseases including coronary heart disease, myocardial infarction, hypertension, atrial fibrillation, hyperlipidaemia, viral myocarditis, chronic heart failure and pulmonary heart disease. However, the protective effects of breviscapine on cardiovascular diseases based on experimental studies along with its underlying mechanisms have not been reviewed systematically. This paper reviewed the underlying pharmacological mechanisms in the potential cardioprotective effects of breviscapine and elucidated its clinical applications.